Step-by-step explanation:
Substitute the y in the 1st equation with the 2nd equation.
7x + 10(2x + 9) = 36
7x + 20x + 90 = 36
27x + 90 = 36
3x + 10 = 4
3x = -6
x = -2
So now we can find y.
y = 2x + 9 = 2(-2) + 9 = (-4) + 9 = 5.
So x = -2, y = 5.
Answer:
$8,029.91
Step-by-step explanation:
You have to use the exponential growth equation:
A=P(1+r)^t
Where A is the final amount, P is the initial amount, r is the rate of increase, and t is the time in years. So:
A=6,600(1+0.04)^5
(The rate has to be changed into a decimal)
Then, just plug this equation into a calculator (without the A= part, so just 6,600(1+0.04)^5) and you'll get the answer.
Answer: y=12 x =9
Step-by-step explanation:
In a parallelogram the diagonals bisect each other making them equal.
this means 2y + 6 = 30
we can rearrange this as 30 - 6 = 2y
24 = 2y therefore y = 12
3x - 3 = 24
We can rearrange this as 24 + 3 = 3x
3x = 27
27 / 3 = 9
x = 9
Hope this helped :)